Pengaruh susunan media filter dalam kolom filtrasi terhadap penurunan kadar besi (Fe), mangan (Mn), dan kekeruhan air sumur di Kabupaten Manokwari - Mangallo, Bertha; Ambraw, Samuel; Dyah N. Lestari, Agnes; Mangallo, David; Budi Santoso, Bimo (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: The quality of groundwater is significantly influenced by the mineral composition of the surrounding rocks and soil in the aquifer. High concentrations of minerals, particularly iron (Fe) and manganese (Mn), can cause discoloration typically a yellow-brown hue and an unpleasant taste in the water. This study aims to evaluate the effect of different filter media arrangements in a filtration column on the reduction of Fe, Mn, and turbidity levels in well water. The natural filter media used include sand, gravel, palm fiber, and activated carbon, arranged within a filtration column model. Water samples were taken from dug wells in Sowi 2 Village and a drilled well in Susweni, Manokwari Regency. Initial characterization of the water samples included assessments of odor, color, turbidity, and Fe and Mn concentrations. Results indicate that during the rainy season, well water from Sowi 2 meets clean water quality standards based on pH, turbidity, and Fe and Mn content. However, the drilled well in Susweni exceeds acceptable limits in terms of color and pH. Filtration using the designed column and selected natural media effectively reduced Fe, Mn, and turbidity. Turbidity reduction reached 100% in both column A and B. Fe concentration was reduced by 78.53% in column A and 73.55% in column B. Mn concentration was reduced by 76% in column A and 65.45% in column B.